tif-Stimulated deoxyribonucleic acid repair in Escherichia coli K-12. - Castellazzi, M (1980)
Bacterial survival is significantly increased after ultraviolet irradiation in tif sfi cells, provided that the thermosensitive tif mutation has been expressed at 41 degrees C before irradiation. This tif-mediated "reactivation of ultraviolet irradiated bacteria" needs de novo protein synthesis, as is the case for the tif-mediated reactivation of ultraviolet-irradiated phage lambda. However, in striking contrast to the phage reactivation process, this tif-mediated reactivation is no longer associated with mutagenesis. It also requires the presence of the uvrA+ excision function. These results strongly suggest the existence in Escherichia coli K-12 of a repair pathway acting on bacterial deoxyribonucleic acid which is inducible, error free, and uvr dependent.